TEMPORAL ANALYSIS OF SUICIDE MORTALITY IN THE BRAZIL NORTHEAST (Cadernos ESP, 2024)
Suicide is a serious public health issue that requires detailed analysis for the formulation of effective policies. This study examined suicide mortality in the Northeast Region of Brazil between 2013 and 2022 with the aim of identifying trends and regional patterns. Using data from the Mortality Information System (SIM), 30,047 deaths classified by age, sex, marital status, and location of occurrence were analyzed. The methodology included an ecological time series design and Prais-Winsten generalized linear regression to correct for serial autocorrelation. A 48% increase in the suicide mortality rate was observed, rising from 4.47 to 6.61 per 100,000 inhabitants. The average annual percentage change (APC) was 5.03%, indicating an increasing trend. The results highlight the urgent need for targeted regional policies for suicide prevention and strengthening mental health support.
Keywords: Suicide; Mortality; Social Work; Spatiotemporal Analysis